Determining a safe-distance guideline for helicopters near a wind turbine and wind park - Bakker, R.; Geest, P. van der (My University, 2018)
The Netherlands Aerospace Centre (NLR) was tasked to support the (former) Netherlands Ministry of Infrastructure and Environment to define a safe distance guideline for helicopters with respect to wind turbine parks. In an exploratory research, based on a relatively simple analytical wake model, a guideline for safe distance for helicopters is determined that can be used to support helicopter operations near offshore wind turbines and wind farms. The paper discusses the wake model, the safe distance criteria and will also consider the influence of the turbulence intensity, the wind turbine shaft height, rotor diameter of the turbine and the safe distance with regards to a multiple turbines in a wind park. A guideline for a safe distance is determined that could support directives for safe offshore helicopter operations near wind turbines.